Application of Warm Lemongrass Compress Therapy on Mr. D with Gout Arthritis - Kamila, Sri; Marisa, Dewi Erna; Purbaningsih, Endah Sari; Karlina, Nonok (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Gout arthritis is a joint condition caused by elevated blood uric acid levels. One non-pharmacological therapy that can be administered is the application of warm compresses made from boiled lemongrass to alleviate pain. This study aims to determine the effect of applying warm compresses made from boiled lemongrass on Mrs. R, who has gout arthritis. Method: A case study was used, with the subject being a family that includes a member with gout arthritis. Data collection was conducted by first identifying nursing care needs. Data collection instruments included a family nursing care assessment form and the Standard Operating Procedure (SOP) for warm compress therapy using boiled lemongrass. The warm compress therapy using boiled lemongrass was administered for 20 minutes over three days. Result: The case study results showed that the warm compress therapy using boiled lemongrass was effective in reducing chronic pain in Mrs. R, who has gout arthritis. Conclusion: The warm compress therapy using boiled lemongrass was effective in reducing pain in Mrs. R, who has gout arthritis.